Effects of Naringin on Cardiomyocytes From a Rodent Model of Type 2 Diabetes - Uryash, A.; Mijares, A.; Flores, V.; Adams, J. A.; Lopez, J. R. (Frontiers in Pharmacology, 2021)
Diabetic cardiomyopathy (DCM) is a primary disease in diabetic patients characterized by diastolic dysfunction leading to heart failure and death. Unfortunately, even tight glycemic control has not been effective in its prevention. We have found aberrant diastolic Ca2+ concentrations ([Ca2+]d), decreased glucose transport, elevated production of reactive oxygen species (ROS), and increased calpain activity in cardiomyocytes from a murine model (db/db) of type 2 diabetes (T2D). Furthermore, cardiomyocytes from these mice demonstrate significant cell injury, increased levels of tumor necrosis factor-alpha and interleukin-6 and expression of the transcription nuclear factor-κB (NF-B), decreased cell viability, and reduced expression of Kir6.2, SUR1, and SUR2 subunits of the ATP-sensitive potassium (KATP) channels. Treatment of T2D mice with the citrus fruit flavonoid naringin for four weeks protected cardiomyocytes by reducing diastolic Ca2+ overload, improving glucose transport, lowering ROS production, and suppressed myocardial inflammation. In addition, naringin reduced calpain activity, decreased cardiac injury, increased cell viability, and restored the protein expression of Kir6.2, SUR1, and SUR2 subunits of the KATP channels. Administration of the KATP channel inhibitor glibenclamide caused a further increase in [Ca2+]d in T2D cardiomyocytes and abolished the naringin effect on [Ca2+]d. Nicorandil, a KATP channel opener, and nitric oxide donor drug mimic the naringin effect on [Ca2+]d in T2D cardiomyocyte; however, it aggravated the hyperglycemia in T2D mice. These data add new insights into the mechanisms underlying the beneficial effects of naringin in T2D cardiomyopathy, thus suggesting a novel approach to treating this cardiovascular complication.